Drought, fire and grazing precursors to large‐scale pine forest decline. Issue 7 (12th March 2021) - Connor, Simon E.; Araújo, João; Boski, Tomasz; Gomes, Ana; Gomes, Sandra D.; Leira, Manel; Freitas, Maria da Conceição; Andrade, Cesar; Morales‐Molino, César; Franco‐Múgica, Fátima; Akindola, Rufus B.; Vannière, Boris
Abstract: Aim: Temperate forests are currently facing multiple stresses due to climate change, biological invasions, habitat fragmentation and fire regime change. How these stressors interact with each other influences how, when and whether ecosystems recover, or whether they adapt or transition to a different ecological state. Because forest recovery or collapse may take longer than a human lifetime, predicting the outcomes of different stressor combinations remains difficult. A clearer vision of future forest trajectories in a changing world may be gained by examining collapses of forests in the past. Here, we use long‐term ecological data to conduct a post‐mortem examination of the decline of maritime pine forests ( Pinus pinaster Ait.) on the SW Iberian Peninsula 7000–6500 years ago. Location: Portugal and Spain. Methods: We compared four palaeoecological records—two with pine declines and two without—using a multiproxy approach. Bioclimatic differences between the four sites were explored. Proxies for past vegetation and disturbance (fire and grazing) were compared with independent palaeoclimatic records. We performed functional traits analysis and used phase plots to examine the causes of pine decline. Results: The pine decline represents a critical transition in SW Iberia, which lies close to maritime pine's bioclimatic limits. Prolonged drought likely killed trees and suppressed the fires that normally stimulate pine germination and pinewood recovery. Increased grazing pressure facilitated the rapid spread of resprouter shrubs. These competed with pine trees and ultimately replaced them. Our data highlight complex interactions between climate, fire, grazing and forest resilience. Main Conclusions: The pine decline occurred at least a century after post‐fire resprouters overtook obligate seeders in the vegetation, constituting an early‐warning signal of forest loss. Fire suppression, resprouter encroachment and grazing may threaten the persistence of Mediterranean forests as droughts become more frequent and extreme.